2014
DOI: 10.1371/journal.pone.0113069
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Evolution and Affinity-Maturation with Coliphage Qβ Display

Abstract: The Escherichia coli bacteriophage, Qβ (Coliphage Qβ), offers a favorable alternative to M13 for in vitro evolution of displayed peptides and proteins due to high mutagenesis rates in Qβ RNA replication that better simulate the affinity maturation processes of the immune response. We describe a benchtop in vitro evolution system using Qβ display of the VP1 G-H loop peptide of foot-and-mouth disease virus (FMDV). DNA encoding the G-H loop was fused to the A1 minor coat protein of Qβ resulting in a replication-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(85 citation statements)
references
References 43 publications
3
82
0
Order By: Relevance
“…The A1 protein is incorporated in 3-10 copies per virion, or in 12 copies in accordance with a recent study [32], it is required for infection, but its precise function is not known [for more references, see [8,29,30,31,32,33]]. A recent electron microscopy visualization of foreign epitopes carried by A1 protein within infectious Qβ particles showed that the A1 protein molecules are occupying corners of the Qβ icosahedron [32]. The lysis protein forms pores in the cellular membrane, leading to activation of autolysins and, eventually, cell lysis [34].…”
Section: Family Of Rna Phagessupporting
confidence: 75%
See 2 more Smart Citations
“…The A1 protein is incorporated in 3-10 copies per virion, or in 12 copies in accordance with a recent study [32], it is required for infection, but its precise function is not known [for more references, see [8,29,30,31,32,33]]. A recent electron microscopy visualization of foreign epitopes carried by A1 protein within infectious Qβ particles showed that the A1 protein molecules are occupying corners of the Qβ icosahedron [32]. The lysis protein forms pores in the cellular membrane, leading to activation of autolysins and, eventually, cell lysis [34].…”
Section: Family Of Rna Phagessupporting
confidence: 75%
“…In addition to the standard maturation protein, CP, and replicase subunit, the Allolevivirus genome encodes a C-terminally extended CP known as the minor A1 protein, which appears as a result of ribosomal read-through of a leaky opal termination codon of the CP gene [28] and is essential for the formation of viable Qβ particles in vivo [29,30,31]. The A1 protein is incorporated in 3-10 copies per virion, or in 12 copies in accordance with a recent study [32], it is required for infection, but its precise function is not known [for more references, see [8,29,30,31,32,33]]. A recent electron microscopy visualization of foreign epitopes carried by A1 protein within infectious Qβ particles showed that the A1 protein molecules are occupying corners of the Qβ icosahedron [32].…”
Section: Family Of Rna Phagessupporting
confidence: 56%
See 1 more Smart Citation
“…Phage display is one of the most commonly used methods for in vitro peptide‐screening . Many types of phage can be used in phage display technique, including filamentous bacteriophage, T4 phage, T7 phage, Qβ phage, etc . To be displayed on phage particles, cyclic peptides should be fused to solvent‐exposed surface proteins, such as pIII, pVI, pVII, pVIII, and pIX proteins .…”
Section: Strategies To Develop Cyclic Peptides Into Therapeutic Agentsmentioning
confidence: 99%
“…In this study we have determined in low and high malaria transmission areas the impact of dual HIV-malaria infection on IgG subclass responses to two conserved P. falciparum derived asexual blood stage antigens displayed separately upon a recombinant RNA coliphage Qβ as previously described by our group (14, 15). The recombinant phage QβMSP3 displays the conserved C-terminal 88 aa of the merozoite surface protein 3 (16, 17) whilst QβUB05 bears the previously described malaria antigen UBO5 (18).…”
Section: Introductionmentioning
confidence: 99%